2021
DOI: 10.1007/s00238-021-01798-1
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of living animal models in microsurgical training: beyond technical expertise

Abstract: Background Many studies are investigating the role of living and nonliving models to train microsurgeons. There is controversy around which modalities account for the best microsurgical training. In this study, we aim to provide a systematic literature review of the practical modalities in microsurgery training and compare the living and nonliving models, emphasizing the superiority of the former. We introduce the concept of non-technical skill acquisition in microsurgical training with the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 109 publications
0
23
0
Order By: Relevance
“…Although several studies demonstrated that the additional time spent exercising on nonliving tissue models improves the acquisition of technical skills in microsurgery, 3 4 5 working on living tissue models remained an important aspect. 2…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies demonstrated that the additional time spent exercising on nonliving tissue models improves the acquisition of technical skills in microsurgery, 3 4 5 working on living tissue models remained an important aspect. 2…”
Section: Discussionmentioning
confidence: 99%
“…The requirement of live animals for surgical training is of particular interest for many researchers (27)(28)(29). Nevertheless, most surgeons consider that adequate microsurgical training can be completed without live models, and the current effort is to attempt to minimize the use of live animals (30,31). The use of virtual and augmented reality devices will hopefully be a powerful adjunct to microsurgical training, but these tools still require a thorough validation (32).…”
Section: Future Directionsmentioning
confidence: 99%
“…They offer the opportunity to practice dissection and perform vascular anastomosis, flaps and finally reconstructions techniques, and organs transplantations. Living models not only provides conditions similar to human tissue but also provide excellent feedback of anastomosis patency [7].…”
Section: Living Modelsmentioning
confidence: 99%
“…The chicken thigh model was validated in several studies as it closely reflects arterial anastomosis in the human hand in terms of both -size of the anastomosis and required tissue care [10][11][12]. Furthermore, non-living models are cost-efficient and do not interfere with ethical issues, but provide no feedback about the anastomosis function, blood flow, or tendency to thrombosis [7].…”
Section: Non-living Modelsmentioning
confidence: 99%
See 1 more Smart Citation